If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 = (0.5) * 9x + 12 Reorder the terms: 7 + 4x = (0.5) * 9x + 12 Multiply 0.5 * 9 7 + 4x = 4.5x + 12 Reorder the terms: 7 + 4x = 12 + 4.5x Solving 7 + 4x = 12 + 4.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.5x' to each side of the equation. 7 + 4x + -4.5x = 12 + 4.5x + -4.5x Combine like terms: 4x + -4.5x = -0.5x 7 + -0.5x = 12 + 4.5x + -4.5x Combine like terms: 4.5x + -4.5x = 0.0 7 + -0.5x = 12 + 0.0 7 + -0.5x = 12 Add '-7' to each side of the equation. 7 + -7 + -0.5x = 12 + -7 Combine like terms: 7 + -7 = 0 0 + -0.5x = 12 + -7 -0.5x = 12 + -7 Combine like terms: 12 + -7 = 5 -0.5x = 5 Divide each side by '-0.5'. x = -10 Simplifying x = -10
| 5+3u=20 | | 3(x-2)+4=2x-6+x | | 5(2x-1)=3(x-1)+5 | | 3x-3=3x+6 | | 145-u=237 | | 2(5-c)= | | 6(x-30)=150+12x | | -2(x-2)-2=x+-x+5 | | y-x=5 | | 8(y-1)=3y-28 | | 38=(2w-7)+2w | | 4x+2(x-1)=x+2x-11 | | 4x^2-38=1833 | | 39=(2w-7)+2w | | 6x-4+3x=5x+14 | | (x+3)=-2(x+6) | | a-2b+c=8 | | x-3x-7=0 | | 2a+b+c=-6 | | 2x+y=3 | | 24-7x-72=16+x | | 2x+3=x-2kx-5 | | 4(2x-1)=5(x-2) | | 8(x-2)+4=5x+x+8 | | 8p-5p+-15=21p-3 | | 5x+7=x-1 | | 4x+7x-6x=5+4x+4 | | 4x+3+3x+38=90 | | 2x-3=6x-6 | | x^2+41-1=0 | | y=3x-2 | | 2m-7=17 |